Kajian Literatur: Membangun Kepercayaan di Era Digital: Dampak Aktivitas Pemasaran Media Sosial terhadap Loyalitas Pelanggan UMKM - M Aziz Ramadhani; Vika Wulandari; Natasya Priskilla Singal; Nazhira Harghea Zalianti; Nandha Narendra Muvano (Shofanah Media Berkah, 2026)
Micro, Small, and Medium Enterprises (MSMEs) face significant challenges regarding limited market access and competitiveness in the digital era. This study aims to analyze the strategic role of digital technology, particularly social media and content marketing, as an empowerment tool for MSMEs. The methodology employed across the sources includes literature studies, quantitative surveys, and in-depth interviews with business actors. The results indicate that the consistent use of platforms such as Instagram and TikTok effectively increases product visibility, reaches global audiences, and strengthens emotional connections with consumers through real-time interaction. Creative content strategies involving high-quality visual aesthetics and storytelling are proven significant in driving customer engagement and sales conversion. However, the main obstacles found are low digital literacy and limited resources in managing content consistently. In conclusion, the integration of social media and digital marketing innovation is the primary key for MSMEs to enhance global competitiveness and ensure business sustainability. Continuous support in the form of technical training is required to maximize the potential of the digital ecosystem optimally.